Pre-transplant CD200 and CD200R1 concentrations are associated with post-transplant events in kidney transplant recipients. Issue 37 (September 2019) - Oweira, Hani; Khajeh, Elias; Mohammadi, Sara; Ghamarnejad, Omid; Daniel, Volker; Schnitzler, Paul; Golriz, Mohammad; Mieth, Markus; Morath, Christian; Zeier, Martin; Mehrabi, Arianeb; Sadeghi, Mahmoud
Abstract : Abstract: CD200 is an immunoglobulin superfamily membrane protein that binds to a myeloid cell-specific receptor and induces inhibitory signaling. The aim of this study was to investigate the role of CD200 and its receptor (CD200R1) on kidney transplant (KTx) outcome. In a collective of 125 kidney recipients (University hospital, Heidelberg, Germany), CD200 and CD200R1 concentrations were evaluated immediately before transplantation. Recipient baseline and clinical characteristics and KTx outcome, including acute rejection (AR), acute tubular necrosis, delayed graft function, cytomegalovirus (CMV) and human polyomaviridae (BK) virus infections, and graft loss were evaluated during the first post-transplant year. The association of CD200 and CD200R1 concentrations and CD200R1/CD200 ratios with the outcome of KTx was investigated for the first time in a clinical setting in a prospective cohort. There was a positive association between pre-transplant CD200R1 concentrations and CMV (re)activation ( P = .041). Also, increased CD200R1 concentration was associated with a longer duration of CMV infection ( P = .049). Both the frequency of AR and levels of creatinine (3 and 6 months after KTx) were significantly higher in patients with an increased CD200R1/CD200 ratio (median: 126 vs 78, P = .008). Increased pre-transplant CD200R1/CD200 ratios predict immunocompetence and risk of AR, whereas high CD200R1 concentrations predict immunosuppression and high risk of severe CMV (re)activation after KTx.